From the heart of the Church - Marchionni, Paolo (Medicina e Morale, 1990)
In recent weeks, the Apostolic Constitution of John Paul II on Catholic Universities, entitled Ex corde ecclesiae, was published. This document, which bears the date 15 August, the Solemnity of the Assumption of the Blessed Virgin Mary, is intended to be a kind of reference text, a sort of 'magna charta' (n. 8) to which all Catholic Universities on the various continents must refer to in order to continue their mission to seek and serve the truth.